Utilization Of Waste From Vco Production As A Nata De Coco Stater ToIncrease The Income Of The People Of Kwt “Bengke Sakato”.: Pemanfaatan Limbah Pembuatan VCO Menjadi Stater Nata De CocoUntuk Meningkatkan Pendapatan Masyarakat KWT”Bengke Sakato” - Suryani, Suryani; Helga Yermadona; Nurhaida Nurhaida; Adelia Pramita Sari; Yunita Sabri; Rahmawati Rahmawati; Femi Earnestly (Journal of Community Service and Application of Science, 2022)
The service partner of KWT "Bengke Sakato" Sungai Sariak, Padang PariamanRegency, chaired by Ermatius. So far, his line of business is manufacturing VCO with the brand "Amboko" and processing 2000 coconuts every month. With the number of members as many as 25 people, this income is not sufficient. Waste from the VCO manufacturing process has not been utilized such as coconut water, coconut fiber, and coconut shells are still wasted. Whereas coconut water can be made into the starter and Nata de coco, the coir can be made cocopeat and the shell can be made of ceramics or bags that can increase income. This service program aims to empower and improve the community's economy. Namely the community members of KWT "Bengke Sakato". The method of service is that it begins with socialization, then carries out a workshop, after which monitoring and evaluation are carried out, as well as mentoring. This activity can produce starter or nata de coco seeds from pineapple and coconut water, where every 3 liters of coconut water and one pineapple produces 5 starter bottles with a price per bottle of IDR 50,000. In addition, it can also increase the knowledge of partners from 29.3% to 87.3%. It can be concluded that this service activity can increase partner knowledge about the manufacture of nata de coco seeds from coconut water which is a waste of the VCO process. And can improve the partner's economy. Making Nata de coco starter from coconut water can increase family income or empower the community.